Faktor-Faktor Yang Mempengaruhi Penerapan Standar Akuntansi Pemerintah Pada Pemerintah Kota Baubau - Khayatun Nufus (Institut Teknologi dan Bisnis Ahmad Dahlan Jakarta, 2014)
The Government Accounting Standards (SAP) is the accounting principles used for financial reporting and Government Performance. Regional autonomy encourage governments to make regulation in the management and reporting financial statements. The necessity and demands transparency of financial performance provides an overview of importance of local government accounting standards to be applied so that there will be uniformity in the assessment of local government performance. This paper presents the results that the quality of human resources, and political simultaneously significant effect on the implementation of SAP in the Baubau Municipality.